Implementasi Digitalisasi dan Teknologi Untuk Perkembangan dan Strategi Bisnis Kru V Jasa Pengelola Sosial Media dari Sisi Pemasaran - Bobby Dewantoro; Moh. Farid Hidayat; Talita Karisma Syaharani; Anggita Dana Salsa Bila; Rheiza Marell Anugerah (Jurnal Riset dan Inovasi Manajemen, 2024)
This journal discusses the implementation of digitization and technology as key drivers for advancing and designing business strategies for Kru V, a social media management service agency. In an era where social media plays a crucial role in marketing and customer interaction, the agency leverages digital technology to enhance operational efficiency and broaden the scope of its services. This article provides an in-depth analysis of the concrete steps taken by Kru V in adopting cutting-edge technology and its impact on the agency's business development and competitive advantage.